2004
DOI: 10.1590/s1676-06032004000100008
|View full text |Cite
|
Sign up to set email alerts
|

Checklist of the Trichoptera (Insecta) of Brazil I

Abstract: We present here a list of Trichoptera species recorded in the literature from Brazil as of September 2003. The total number of species recorded for Brazil is 378. The most diverse family is Hydropsychidae with 103 species; the second most diverse is Hydroptilidae with 50 species, followed by Leptoceridae and Philopotamidae with 41 each. Distributions by state and additional literature relevant to Brazilian Trichoptera are also presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
142
0
26

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(170 citation statements)
references
References 34 publications
2
142
0
26
Order By: Relevance
“…Abbreviations: d lob -dorsal lobe; inf app -inferior appendage; m pro -membranous processes; mv pro -mesoventral process; sg pl -subgenital plate; sg pro -subgenital processes; VII -sternum VII; VIII -segment VIII; IX -sternum IX. Oxyethira lagunita Flint, 1982PR (Kelley 1984, Paprocki et al 2004 Oxyethira spissa Kelley, 1983AM, PA (Kelley 1984, Paprocki et al 2004 Oxyethira ( Oxyethira bettyae Thomson & Holzenthal, 2012PE (Souza et al 2013 Oxyethira bicornuta Kelley, 1983AM (Kelley 1983, Paprocki et al 2004 Oxyethira espinada Holzenthal & Harris, 1992 AL ( …”
Section: Female and Immatures Unknownmentioning
confidence: 99%
See 1 more Smart Citation
“…Abbreviations: d lob -dorsal lobe; inf app -inferior appendage; m pro -membranous processes; mv pro -mesoventral process; sg pl -subgenital plate; sg pro -subgenital processes; VII -sternum VII; VIII -segment VIII; IX -sternum IX. Oxyethira lagunita Flint, 1982PR (Kelley 1984, Paprocki et al 2004 Oxyethira spissa Kelley, 1983AM, PA (Kelley 1984, Paprocki et al 2004 Oxyethira ( Oxyethira bettyae Thomson & Holzenthal, 2012PE (Souza et al 2013 Oxyethira bicornuta Kelley, 1983AM (Kelley 1983, Paprocki et al 2004 Oxyethira espinada Holzenthal & Harris, 1992 AL ( …”
Section: Female and Immatures Unknownmentioning
confidence: 99%
“…Oxyethira brasiliensis Kelley, 1983PA (Kelley 1983, Paprocki et al 2004 Oxyethira diplospissa Oxyethira maranhensis Santos, 2017 MA (Souza and Oxyethira rafaeli Santos, 2017 BA, PI (Souza and …”
Section: Incertae Sedismentioning
confidence: 99%
“…A família Hydropsychidae foi proposta por Curtis em 1835 e compreende a segunda maior família de Trichoptera (atrás apenas de Hydroptilidae), com aproximadamente 1.800 espécies conhecidas mundialmente (Morse 2014), pouco mais de 400 para a Região Neotropical (Flint et al 1999) e mais de 100 espécies conhecidas para o Brasil (PaProCki et al 2004), as quais estão distribuídas em 9 dos 15 gêneros neotropicais da família (Flint et al 1999). Para o Estado de São Paulo são registradas 33 espécies para a família (Calor 2011).…”
Section: _____________________________________unclassified
“…A família Leptoceridae foi proposta por Leach em 1815 e compreende a terceira maior família de Trichoptera, com um pouco menos que 1.800 espécies descritas e 48 gêneros viventes (Morse 2014), cerca de 150 espécies com registro para a região Neotropical (Flint et al 1999) e aproximadamente 40 espécies conhecidas para o Brasil (PaProCki et al 2004). Para o Estado de São Paulo, 26 espécies da família são registradas (Quinteiro & Calor 2012 O material foi preservado de dois modos: em via seca no caso de parte dos adultos coletados com rede entomológica e no lençol, e em via úmida (em álcool 80%) no caso dos espécimes coletados nas bandejas e no restante do material coletado com rede entomológica e no lençol.…”
Section: _____________________________________unclassified
“…Paprocki et al (2004) reported only 378 species in 61 genera, and Santos et al (2015) elevated it 642 species and 70 genera. In last decades, some publications on distributional notes or regional checklists are were published (e.g., Blahnik et al, 2004;Dumas et al, 2010;Calor, 2011;Nogueira & Cabette, 2011;Quinteiro et al, 2014) and around 100 new species were described from Brazil, but there are at least another 300 new species to be described, deposited in museums (Calor, 2011).…”
mentioning
confidence: 99%